ANALISIS KEMAMPUAN KREATIVITAS DAN KONEKSI MATEMATIS TERHADAP PRESTASI BELAJAR SISWA SMA - Marpaung, Melda Melina Siska; Tambunan, Hardi; Pangaribuan, Firman (Universitas Quality, 2024)
This research aims to describe the relationship between creativity abilities and mathematical connections with high school students' learning achievement which is analyzed using correlation analysis. This research is quantitative research. The research population included all phase E class students at SMA Negeri 1 Salak. The sample was 146 students from 8 phase E classes determined by cluster sampling. Data collection was carried out using tests and questionnaires. The data analysis technique used is partial correlation analysis. The results of the research show that creativity abilities and mathematical connections are jointly related to high school students' learning achievement, where the contribution given is 46.3%, and the regression equation obtained is Y = 0.97 + 0.422X1 + 0.059 X2. The relationship between creative ability (X1) and learning achievement (Y) with a contribution of 23.27%. The relationship between mathematical connection ability (X2) and learning achievement with a contribution of 3.59%.